National Herbarium Plant Collecting Programme reveals new country and provincial distribution records from South African National Parks (Apocynaceae, Asteraceae & Xanthorrhoeaceae: Asphodeloideae) - Bester, Stoffel P.; Herman, Paul P.j.; Klopper, Ronell R. (Phytotaxa, 2012)
New country and provincial distribution records for South Africa of specimens collected mainly in various South African National Parks are reported on here. The taxa included in this contribution are of Orthanthera albida (Apocynaceae), Doellia cafra (Asteraceae), Bulbine ophiophylla (Xanthorrhoeaceae: Asphodeloideae) and Trachyandra asperata var. basutoensis (Xanthorrhoeaceae: Asphodeloideae).